2003
DOI: 10.1097/00001813-200307000-00011
|View full text |Cite
|
Sign up to set email alerts
|

NB1011 induces Ser15 phosphorylation of p53 and activates the G2/M checkpoint

Abstract: NB1011, a phosphoramidate derivative of (E)-5-(2-bromovinyl)-2'-deoxyuridine, is a novel anti-cancer agent that selectively targets tumor cells expressing high levels of thymidylate synthase (TS), an enzyme required for DNA biosynthesis. NB1011 treatment of high-TS-expressing breast carcinoma cells (MCF7TDX) results in the induction of p53 and p21 protein levels, whereas no p53 or p21 induction is observed in the low-TS-expressing MCF7 tumor cells. Furthermore, MCF7TDX cells accumulate in the G(2)/M phase of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In G2/M arrest, cdc2, the kinase required for entry into mitosis, is inhibited by various mechanisms. p21 and 14-3-3 σ , which are transcriptional targets of p53, play key roles in inhibiting cdc2 activity (Taylor and Stark, 2001; Dellinger et al , 2003). 14-3-3 σ has been reported to be a critical regulator of the G2/M checkpoint in both p53 wild-type and mutant PC-3 cancer cells (Han et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In G2/M arrest, cdc2, the kinase required for entry into mitosis, is inhibited by various mechanisms. p21 and 14-3-3 σ , which are transcriptional targets of p53, play key roles in inhibiting cdc2 activity (Taylor and Stark, 2001; Dellinger et al , 2003). 14-3-3 σ has been reported to be a critical regulator of the G2/M checkpoint in both p53 wild-type and mutant PC-3 cancer cells (Han et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies into the mechanism of action of thymectacin suggested the involvement of the tumour suppressor p53 and the activation of the G2/M checkpoint eventually contributing to cell cycle arrest. 45 Phase I clinical trials of thymectacin dosed intravenously in patients with advanced colorectal cancer that failed 5-FU treatment was initiated. Initial results using doses ranging from 200 mg/kg to 1250 mg/kg showed that thymectacin was well tolerated and a number of patients achieved a stable disease state.…”
Section: Stampidine and Thymectacinmentioning
confidence: 99%
“…This pointed to a unique nucleotide-mediated labeling of proteins that causes cytotoxicity. Further studies into the mechanism of action of thymectacin suggested the involvement of the tumor suppressor p53 and the activation of the G2/M checkpoint eventually contributing to cell cycle arrest …”
Section: Pronucleotide Clinical Candidatesmentioning
confidence: 99%